Mobile applications at the dentist / Teh Adilla Mustaza, Tong Wah Lim and Siti Mariam Ab. Ghani - Mustaza, Teh Adilla; Lim, Tong Wah; Ab. Ghani, Siti Mariam (Penerbit UiTM (UiTM Press), 2016)
Utilization of Apps in the dental clinics for dental education in Malaysia is currently lacking, and serious transformation is needed to modernize dentistry to empower the dental community in this technological advanced era. The purpose of this study is to develop related Apps that are beneficial to be used in the dental clinics mainly for educational purposes, and to evaluate dental students 'perception towards the usage of these Apps in the dental clinic. Two kinds of Apps were being developed; Apps for patients' dental education in an interactive educational game layout, and Apps for conducting oral health related quality of life survey. Subsequently, an online survey form was then used to gather undergraduate dental students' perception on using these Apps in the dental clinic. The developed Apps were successfully made available in the online market. 114 clinical year dental students of the Faculty of Dentistry Universiti Teknologi MARA participated in this study. The students 'perceptions on the usage of these Apps were found to be positive. 67.5% of the students agreed that these Apps are useful in the dental clinic, 66.7% think that these Apps are beneficial to be downloaded and 68.4% will use these Apps if it is made available freely in the clinic. The willingness of most respondents to use these Apps made it a valuable tool for measuring the quality of dental health information and services being given to the community in a more robust and systematic way.